Gestão de acervo memorialístico: proposta de elaboração de inventário do patrimônio cultural da UFPB - Dias, Lena Leite (2020)
The proposal in question articulates cultural heritage management and preservation within universities in order to think about methodologies and mechanisms that address the theme and, thus, can contribute to enhance a movement of valorization of this heritage in Brazilian universities, considering that these institutions, most of them, need to recognize themselves as cultural heritage, producers of their own patrimony, as well as recipients of patrimonial assets. However, managing all these possibilities becomes a challenge that starts from understanding the concept of cultural heritage. Therefore, this report aims to present, based on the analysis of several descriptive instruments contained in the methodology, based on bibliographic research, and on brazilian legislation, a proposal for the developed Inventory File of Cultural Heritage of the Federal University of Paraíba, considering the macro-category of material and immaterial heritage, understanding it as necessary instrument for the institution's heritage preservation policy.